2019
DOI: 10.1080/03079457.2019.1607966
|View full text |Cite
|
Sign up to set email alerts
|

Development of innate immunity in chicken embryos and newly hatched chicks: a disease control perspective

Abstract: Newly hatched chickens are confronted by a wide array of pathogenic microbes because their adaptive immune defences have limited capabilities to control these pathogens. In such circumstances, and within this age group, innate responses provide a degree of protection. Moreover, as the adaptive immune system is relatively naïve to foreign antigens, synergy with innate defences is critical. This review presents knowledge on the ontogeny of innate immunity in chickens pre-hatch and early post-hatch and provides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 267 publications
(323 reference statements)
1
43
0
4
Order By: Relevance
“…To our knowledge, this the first report of early life cytokine gene expression in organs of CAstV chicks affected by WCS, demonstrating the early activation of the innate immune system of embryos and newly hatched chicks against a viral pathogen, as was previously described [45]. The present study showed that CAstV replicates in the epithelium of the intestine, lymphoid organs, and liver, but the mechanism of the generation of an innate immune response against CAstV infection in these tissues has not been fully characterized, and more studies are needed to elucidate and provide more information regarding this important topic.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…To our knowledge, this the first report of early life cytokine gene expression in organs of CAstV chicks affected by WCS, demonstrating the early activation of the innate immune system of embryos and newly hatched chicks against a viral pathogen, as was previously described [45]. The present study showed that CAstV replicates in the epithelium of the intestine, lymphoid organs, and liver, but the mechanism of the generation of an innate immune response against CAstV infection in these tissues has not been fully characterized, and more studies are needed to elucidate and provide more information regarding this important topic.…”
Section: Discussionsupporting
confidence: 73%
“…These are non-acute, late immune responses. However, the affected studied animals had merely a few hours of life, so it can be speculated that this could be due to the fact that the immune responses are still immature or did not have enough time to develop [45].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic expression of TLRs may indicate the chances of genetic modulation and production of enhanced immunological response due to higher expression levels of TLRs in chicken. The TLR2 and TLR4 are only expressed on the surface of DCs, natural killer (NK) cells, and monocytes, but intracellular expression has also been noticed in the endothelial cells (Tamiru et al, 2019). Similarly, NK cells use a variety of cellular receptors, such as Ly49 and CD94 to induce immunological responses (Boudreau and Hsu, 2018).…”
Section: Expression Patterns Of Tlrs During Different Avian Diseasesmentioning
confidence: 99%
“…Glucocorticoid exposure to the developing brain induces alterations in gene expression, and causes a hyperresponsive HPA axis and increased anxiety behavior. Moreover, the immune function of the late embryonic and neonatal chickens is also not yet entirely developed and undergoes age-dependent variations in respect of structure and occurrence of lymphoid organs as well as immune cell distribution [200][201][202][203]. It is well known that early life experiences have long-term effects on physiology and behavior later in life in poultry [204,205].…”
Section: Research Gaps and Recommendationsmentioning
confidence: 99%